Advance care planning for adolescents with cancer and their parents: study protocol of the BOOST pACP multi-centre randomised controlled trial and process evaluation - Anne van Driessche; Aline De Vleminck; Joni Gilissen; Marijke C. Kars; Jutte van der Werff ten Bosch; Luc Deliens; Joachim Cohen; Kim Beernaert (BMC, 2021)
Abstract Background Research has highlighted the need for evidence-based interventions to improve paediatric advance care planning (pACP) in adolescents with cancer. Although adolescents express the desire and ability to share their values, beliefs and preferences for treatment, there is a lack of structured multicomponent interventions to improve parent-adolescent communication on different ACP themes including those not limited to end-of-life care. The aim of this study is to evaluate the effectiveness and implementation, context and mechanisms of impact of a novel ACP program in paediatric oncology. Methods We will conduct a multi-centre parallel-group randomised controlled superiority trial with embedded mixed-methods process evaluation in Flanders, Belgium. Adolescents aged 10-18 who have cancer, and their parent(s) will be recruited via all four university hospitals in Flanders, Belgium, and support groups. Families will be randomised to receive care as usual or the multicomponent BOOST pACP program, consisting of three conversation sessions between an external facilitator and the adolescent and parent(s). The primary endpoint is improved parent-adolescent communication from the perspective of the adolescent. Secondary endpoints are adolescents' and parents' attitudes, self-efficacy, intention and behaviour regarding talking about ACP themes with each other, parents' perspective of shared decision making in the last clinical encounter, and the paediatric oncologist's intention and behaviour regarding talking about ACP themes with the family. Measurements will be performed at baseline, at 3 months and at 7 months using structured self-reported questionnaires. We will perform a process evaluation in the intervention group, with measurement throughout and post-intervention, using structured diaries filled out by the facilitators, interviews with facilitators, interviews with involved paediatric oncology teams, and audio-recordings of the BOOST pACP conversations. Discussion The BOOST pACP program has been developed to stimulate conversations on ACP themes between parent(s) and the adolescents, simultaneously lowering the threshold to discuss similar themes with healthcare professionals, initiating a process of normalization and integration of ACP in standard care. This combined outcome and process evaluation aims to contribute to building the necessary evidence to improve ACP in paediatric oncology. Trial registration The study is registered at ISRCTN, ISRCTN33228289 . Registration date: January 22, 2021.